Custom made ocular prosthesis in elderly patients: A case report - Maretaningtias Dwi Ariani, - (2023)
A 72-year-old female patient came to Prosthodontics Specialist Universitas Airlangga, Dental Hospital, for an eye prosthesis. The patient lost her right eye because of surgery when she was 10 years old. The eye socket was examined and determined to have minimal contractures and no infection, and the eyelid muscles were still good enough to open and close. A custom-made ocular prosthesis was used to create a working model. It began with an eye print using a customized tray and alginate in the defect area, followed by gypsum type 3 filling of the imprint. The patient’s sclera wax model was then made and modified. A redesigned wax model was then used to produce the sclera attempting to draw the iris and pupil after estimating the position and diameter of the iris in the eye socket. The ocular acrylic prosthesis was then polished and color-matched to the contralateral eye. The patient’s eye prosthesis was then implanted. The eye prosthesis was evaluated for aesthetics, retention, and stability. The use of eye prostheses, particularly in elders, can boost their confidence and sociality, allowing them to live a better life. Also, in the treatment of anophthalmia, a custom-made eye prosthesis may be explored.